Explicit and Implicit Trust Criteria in Business Partnerships - Ismagilova, F; Boštjančič, E (KnE Life Sciences, 2018)
Identifying and understanding the similarities and differences between subjective trust criteria in Russian and European business can help offer scientific recommendations for the development of long-term international business cooperation, based on mutual trust, despite the differences between both cultures. The purpose of this study is to describe the relations between the implicit and explicit trust criteria presented in Russian and European studies, and to compare how these criteria are expressed in Russian and European publications from a quantitative perspective. Using the content analysis of European and Russian publications for the period 2005–2015, the following main research questions are considered: (1) Are more references made to explicit trust criteria than implicit trust criteria? (2) Are the explicit criteria focused on a partner’s business mentioned more often than the explicit criteria focused on a partner’s competences and personality? (3) Are more references made to implicit trust criteria in Russian or European scientific articles? As the results reveal, although implicit criteria do not dominate in the subjective trust criteria for business partnerships, they nevertheless have a significant presence. Trust criteria based on characteristics related to business dominate the criteria for a partner’s competences and personality. The differences between explicit and implicit trust criteria in Russian and European publications are not statistically significant. Nevertheless, on average, the difference between implicit and explicit assumptions of confidence is 0.13 in Russian studies and 0.34 in European studies. The study revealed that small companies entering the international market should consider the risks associated with a failure to understand what a business partner considers an implicit sign for triggering business relations and trust. Keywords: trust in business relations, implicit and explicit trust criteria